2021
DOI: 10.1111/add.15589
|View full text |Cite
|
Sign up to set email alerts
|

Changes in alcohol‐related hospital visits during COVID‐19 in New York City

Abstract: Background and Aims Increased alcohol consumption has been proposed as a potential consequence of the coronavirus disease 2019 (COVID‐19) pandemic. There has been little scrutiny of alcohol use behaviors resulting in hospital visits, which is essential to guide pandemic public policy. We aimed to determine whether COVID‐19 peak restrictions were associated with increased hospital visits for alcohol use or withdrawal. Secondary objectives were to describe differences based on age, sex and race, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 27 publications
(33 reference statements)
0
31
0
Order By: Relevance
“…Alcohol withdrawal in the ED has been associated with increased use of critical care resources [9], and frequent ED visits for alcoholrelated presentations have been associated with high relative mortality rates [1,10]. Furthermore, recent studies have demonstrated significant increases in the proportion of alcohol withdrawal-related ED visits during the COVID-19 pandemic, highlighting the rapidly growing burden of alcohol use on EDs across the world [11][12][13][14].…”
mentioning
confidence: 99%
“…Alcohol withdrawal in the ED has been associated with increased use of critical care resources [9], and frequent ED visits for alcoholrelated presentations have been associated with high relative mortality rates [1,10]. Furthermore, recent studies have demonstrated significant increases in the proportion of alcohol withdrawal-related ED visits during the COVID-19 pandemic, highlighting the rapidly growing burden of alcohol use on EDs across the world [11][12][13][14].…”
mentioning
confidence: 99%
“…The average AUDIT scores in males and females were 5.42 ± 6.51 and 2.82 ± 4.80. Based on the classification according to AUDIT scores, the No Problem group (≤ 7) had 9379 (82.1%), the hazardous user group (8)(9)(10)(11)(12)(13)(14) had 1221 (10.7%), and the potential alcoholism group (≥15) had 827 (7.2%) (Table 2) people each. There was a significant difference in age between the three groups (F [2, 11424] = 21.31, p < 0.001, η 2 = 0.004), but the difference did not exceed the lower limit of "small effect size" (i.e., η 2 > 0.010).…”
Section: Descriptive Resultsmentioning
confidence: 99%
“…Alcohol use was reported to be one of the factors associated with higher odds of suicidal behavior during the COVID-19 pandemic [5]. Although some studies in Japan, India, the United States, and Czechia reported that alcohol use decreased [6,7] or that alcohol-related problems did not change [8,9] during the COVID-19 pandemic, other studies in the United States and Norway reported that alcohol use or alcohol-related problems increased [10][11][12][13]. Findings from eight European countries indicated that during the first months of the COVID-19 pandemic, alcohol consumption in the upper decile of drinkers increased, as did the prevalence of heavy drinkers, in contrast to the declining consumption in other groups in the sample [14].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between emergency service utilisation and alcohol during the pandemic is likely to be highly context specific. It will also hugely depend on the pattern of restrictions in place as illustrated by findings from North America [ 26 , 27 ] outlined earlier and evidence from South Africa finding reduced emergency attendances during total and partial alcohol sales bans [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, alcohol‐related visits at accident and emergency departments decreased at the beginning of the pandemic but to a lesser extent than other visits [ 26 ]. In New York City, during the initial COVID‐19 peak in spring 2020, hospital visits for alcohol withdrawal increased while those for alcohol use decreased [ 27 ]. To date, to the best of our knowledge, the impact of COVID‐19 on alcohol‐related ambulance callouts has not been reported.…”
Section: Introductionmentioning
confidence: 99%